Mangabeira fruits (Hancornia speciosa Gomez): a promising fruit of Brazil - M. C. Vieira; E. R. B. Souza; M. S. P. Paula; R. V. Naves; G. D. Silva (Scientific Electronic Archives, 2017)
Mangabeira (Hancornia speciosa Gomez) is a fruit tree, native to Brazil and found in various regions of the country, from the tableland and coastal plains of the Northeast to the savannas of the Midwest, North and Southeast. It is an important component of ecosystems, which occurs mainly in the Cerrado and the Northeast Coast, serving as food for local people and for wildlife (apes and monkeys, birds and insects). Its natural distribution pattern and aggregate occurrence facilitate extraction. The mangaba has a high ascorbic acid content, which places it among the fruits considered rich in vitamin C. There is a lack of information about the diversity and propagation strategies of the species H. speciosa Gomes. It is also important investigations into the characterization of fruits, seeds emergency and development and plant phenology, aspects of pre and post-harvest fruit, among others, remain understudied.  Thus, this review are as objective to transmit information and knowledge about the value and importance of Mangabeira in Brazil.